Maharah al-Qira'ah Learning Planning and Strategies in Improving Islamic Understanding - Mira Hartati; Abdul Halim Hanafi (Ruhama : Islamic Education Journal, 2022)
The learning process is a complex activity, so careful planning is needed so that it can run systematically and more organized. In Arabic learning, the term learning planning is better known as "I'dad" which means a form of planning and is prepared before the learning process is carried out and is more specific. There are at least four elements that must be in the planning, including objectives, supporting resources, strategy and implementation. The steps of the preparation of the learning plan are: first to formulate specific objectives along with the subject matter, secondly to choose learning experiences, third to choose teaching and learning activities, fourth to determine the people involved, fifth to determine the materials, tools and media to be used, sixth to determine physical facilities or pre-facilities, and seventh to determine evaluation and development materials. In order for this maharah al-qira’ah learning process to be more interesting, educators must be skilled in choosing the strategies to be used. In this case, there are several strategies that can be used in the learning process of maharah al-qira’ah, including empety outline, analysis, snow bolling, broken square / text, and card match indexes.